Chemical Composition of Essential Oil of the Aerial Parts of Lepechinia salviae (Lindl.) Epl. from Northern Chile. Issue 3 (4th May 2019) - Díaz, Ramiro; Contreras, Angel; Leonelli, Gina; Tighe, Ricardo; Cerda, Cristian; Piñones, Marlene; Venegas, Judith; Alfaro, Susana
Abstract: Lepechinia salviae (Lindl.) Epling is an endemic species from northern Chile, where it is important medicinal plant. Essential oil from the aerial parts of L. salviae was extracted using hydro-distillation and analyzed using Gas Chromatography linked to a MS detector and a FID detector. Total thirty-four components (99.3 %) were identified; oxygenated sesquiterpenes τ-cadinol (12.84 %), ledol (10.19 %), illudol (10.02 %) and δ-cadinol (8.52 %) were the main constituents found. This study contributes to the knowledge of L. salviae whose essential oil had not been studied yet.